Caspase-8: Friend or Foe in Bortezomib/Lenalidomide-Based Therapy for Myeloma - Zhou, Liang (Frontiers in Oncology, 2022)
Antiproliferation and proapoptosis are two major molecular mechanisms of action of drugs used for the treatment of multiple myeloma. Proteasome inhibitors. such as bortezomib (PS-341), and immunomodulatory drugs (IMiDs), such as lenalidomide, are the two drug types approved for the treatment of myeloma. Bortezomib and lenalidomide activate caspase-8 and promote the apoptosis of myeloma cells. However, caspase-8 inhibition potentiated the antiproliferative effect of lenalidomide and bortezomib in myeloma cells, suggesting that caspase-8 could regulate proliferation and apoptosis in the opposite pathway. In this mini-review, I summarized recent advances in determining the molecular mechanisms of caspase-8 in bortezomib–lenalidomide-based therapy for myeloma and explored the possible functions of caspase-8 in the proliferation and apoptosis of myeloma cells. Furthermore, future directions of caspase-8-based therapy for myeloma have been discussed.